2013
DOI: 10.25011/cim.v36i3.19724
|View full text |Cite
|
Sign up to set email alerts
|

The biodistribution and pharmacokinetic evaluation of choline-bound gold nanoparticles in a human prostate tumor xenograft model

Abstract: e biodistribution and pharmacokinetic evaluation of choline-bound gold nanoparticles in a human prostate tumor xenogra model Abstract Purpose: Gold nanoparticles (GNPs) have attracted signi cant attention in the treatment of cancer due to their potential as novel radiation enhancers, particularly when functionalized with various targeting ligands. e aim of this study was to assess the biodistribution and pharmacokinetic characteristics of a novel choline-bound GNP (choline-GNP) stabilized with polyethelenimine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Studies on AuNPs showed that these nanomaterials do not accumulate in the liver and do not elicit long-term hepatic dysfunction in animal models. 23,24 Data on the clearance of PEGylated gold nanomaterials also showed that once accumulated, gold nanocarriers were gradually cleared from the body. 24 In addition, as recently demonstrated by some of the authors of this study, 16 gold nanocarriers can be degraded within the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on AuNPs showed that these nanomaterials do not accumulate in the liver and do not elicit long-term hepatic dysfunction in animal models. 23,24 Data on the clearance of PEGylated gold nanomaterials also showed that once accumulated, gold nanocarriers were gradually cleared from the body. 24 In addition, as recently demonstrated by some of the authors of this study, 16 gold nanocarriers can be degraded within the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Choline is a ubiquitous molecule in all cells for which overactivity of processing enzymes (choline kinase) has been found in prostate tumors. One study reported development of polyethylene imine (PEI)- and choline-conjugated Au nanoparticles for the purpose of targeting prostate cancer for GNRT (Razzak et al, 2013 ) (Figure 1D ). While no radiation experiments were performed in this study, favorable pharmacokinetics were shown in mice.…”
Section: Gnrtmentioning
confidence: 99%
“…As a support, AuNPs functionalized with thiocholine showed increased uptake in a human prostate tumor model and decreased intrahepatic accumulation compared with unmodified AuNPs. 41 Here, we report an unprecedented approach to prepare novel calixarene-coated gold nanoparticles (CholCalix-AuNPs) using a polycationic amphiphilic choline-calix [4]arene derivative (CholCalix) forming micelles and NADH, known to reduce the Au 3+ ion to AuNPs 42 (Scheme 1A). CholCalix-AuNPs were characterized for structure and optical properties using different techniques including UV−vis and Raman spectroscopies, dynamic light scattering (DLS), and atomic force microscopy (AFM).…”
Section: ■ Introductionmentioning
confidence: 99%